Oncogenic viral infections among Iranian hemodialysis patients: A systematic review - Ghorbani, Nahid; Qorbani, Mostafa; Djalalinia, Shirin; Atoofi, Mehrdad; Tajbakhsh, Ramin; Mansourian, Morteza; Gorabi, Armita; Asayesh, Hamid; Soleimani, Ali; Noroozi, Mehdi (International journal of preventive medicine, 2019)
Introduction: Chronic hemodialysis is a lifesaving procedure for end-stage renal failure patients who may lead to the transmission of oncogenic viral infections discussed as a major cause of liver disease and a potential cause of substantial morbidity and mortality. In this regard, the hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common infections that studied recently. This study aimed to review systematically all available documents on the prevalence of hepatitis D virus (HED), hepatitis E virus (HEV), hepatitis G virus (HGV), human T-lymphotropic virus (HTLV), human immunodeficiency virus (HIV), and Kaposi's sarcoma-associated herpes virus (KSHV) in Iranian hemodialysis patients. Methods: We conducted a comprehensive systematic review of literature on the prevalence and factors associated with HED, HEV, HGV, HTLV, HIV, and KSHV in Iranian hemodialysis patients. Using Medical Subject Headings (MeSH) terms, Emtree, and related equal Persian key words, irrespective of age, date, and language, the main domestic databanks of Barekat, Scientific Information Database (SID), Iran-doc, and also international databases of PubMed and NLM Gateway (for MEDLINE), Institute of Scientific Information (ISI), and SCOPUS searched. Interest outcome of infection prevalence was confirmed based on reported positive tests of blood samples. Since the studied factors are very numerous and there is even a high heterogeneity in each factor, so the meta-analysis was not performed. Results: Based on our search strategy through comprehensive searching, 509 studies were found. From them, 314 articles were from international data bases and others from Iranian data banks. After excluding duplicates and overlapping studies, 41 studies were included in the analysis; 11 studies were relevant to HIV, 10 studies assigned to HEV, and 7 studies belonged to HGV field. The HDV, HTLV1,2, and KSHV were the other research subject areas. The prevalence of HIV, HGV, and HTLV1,2 ranged from 0% to 1.5%, 0% to 24.19%, and 0.6% to 70.4%, respectively, in different provinces. Conclusions: This is the comprehensive systematic review on oncogenic viral infections prevalence in the Iranian hemodialysis patients. Present findings emphasize on requirement to evidence-based practical intervention for better prevention and control of problem. The findings could be used as a scientific evidence for developing related policies and highlighting the future plan of complementary researches.